ANALISIS DAMPAK PENGGUNAAN HANDPHONE TERHADAP INTERAKSI SOSIAL SISWA SEKOLAH DASAR - Nurhayati Nurhayati; Putri Hana Pebriana; Rizki Ananda; Sumianto Sumianto (STKIP Persada Khatulistiwa Sintang, 2023)
The research in this thesis whos motivated by the impact of mobile phone use on elementary school student’s social interactions. The aim this research is to find out the negative and positive impacts of using mobile phones for elementary school students 013 Muara Jalai and how to overcome these impacts. This study uses case study research. Data collection techniques are observation, interviews, documentation and field notes. The results of the study show that the use of mobile phones can provide results of observations and interviews for class IV at elementary school 013 Muara Jalai, so the accompanying problems are found, namely: the negative impact of using mobile phones on students' social interactions, the attitude of children to their friends imitating what is shown on mobile applicationsn, some there are children who dance, like those in the tik tok application, work from home is neglected.